Iff as Conditional Chain

I'm not sure I like how when we want to prove that two statements are equivalent, we typically say "A if and only if B" and we prove it by separately proving "both directions" AB and BA, but when we want to prove three or more statements are equivalent, we typically say "The following are equivalent" and prove a "circular chain" of conditionals (1) ⇒ (2) ⇒ [...] ⇒ (n) ⇒ (1), as if these were different proof strategies. Because really, the "both directions" business is just a special case of the chain-of-conditionals idea: (1) ⇒ (2) ⇒ (1). At the very least, one of my books ought to have mentioned this.

Leave a Reply

Your email address will not be published.